2021
DOI: 10.1371/journal.pcbi.1009085
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing cancer gene expression data through the lens of normal tissue-specificity

Abstract: The genetic alterations that underlie cancer development are highly tissue-specific with the majority of driving alterations occurring in only a few cancer types and with alterations common to multiple cancer types often showing a tissue-specific functional impact. This tissue-specificity means that the biology of normal tissues carries important information regarding the pathophysiology of the associated cancers, information that can be leveraged to improve the power and accuracy of cancer genomic analyses. R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…While studying differences between same type of cancer (for example oral squamous cell carcinoma) at different sites (of oral cavity), the inherent difference between the normal tissues would be highlighted more rather than differences between those that are independent of normal tissue physiology. [46] If not accounted, this phenomenon may lead to erroneous conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…While studying differences between same type of cancer (for example oral squamous cell carcinoma) at different sites (of oral cavity), the inherent difference between the normal tissues would be highlighted more rather than differences between those that are independent of normal tissue physiology. [46] If not accounted, this phenomenon may lead to erroneous conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we demonstrated through an analysis of solid tumor data from The Cancer Genome Atlas (TCGA) [20] and normal tissue data from the Human Protein Atla (HPA) [21] that the association between tissue-specific and cancer-specific expression values, i.e., the ratio of gene expression in a specific tissue or cancer relative to the mean across multiple tissues or cancers, can be used to improve survival analysis, the comparative analysis of distinct cancer types, and the analysis of cancer/normal tissue pairs. Specifically, we found that genes enriched in normal tissues are more likely to be down-regulated in the associated cancer with elevated expression associated with a favorable cancer prognosis (see the ρ cancer/norm and ρ surv columns in and 3 in Frost [19].…”
Section: Introductionmentioning
confidence: 96%
“…Cancer biology is highly tissue and cell type-specific [12][13][14][15][16] with most driving somatic alterations either occuring in only a small number of cancer types, e.g., KRAS mutations in pancreatic, lung and colorectal cancers [17], or having a functional impact that varies between impacted tissues, e.g., germline BRCA1/BRCA2 mutations that only drive cancer in estrogen-sensitive tissues [18]. As we explored in a recent paper [19], this tissue-specificity means that the pattern of gene activity (as quantified by mRNA expression) in normal tissues carries important information regarding the biology of the associated cancer types. In this paper, we demonstrated through an analysis of solid tumor data from The Cancer Genome Atlas (TCGA) [20] and normal tissue data from the Human Protein Atla (HPA) [21] that the association between tissue-specific and cancer-specific expression values, i.e., the ratio of gene expression in a specific tissue or cancer relative to the mean across multiple tissues or cancers, can be used to improve survival analysis, the comparative analysis of distinct cancer types, and the analysis of cancer/normal tissue pairs.…”
Section: Introductionmentioning
confidence: 99%
“…To study immune microenvironmental effects in tumors, researchers developed a new algorithm that takes advantage of the unique properties of the transcription pro le of cancer samples to infer the contents of tumor cells and the different in ltrating normal cells, It is called Estimation of STromal and Immune cells in MAlignant tumor tissues using Expression data(ESTIMATE) [12,13] . ESTIMATE focuses on stromal and immune cells, which make up the majority of non-tumor components in tumor samples, and identi es speci c signals associated with stromal and immune cell in ltration in tumor tissue [13] .…”
Section: Introductionmentioning
confidence: 99%